Preferencias TRATADOS HIPOCRÁTICOS SOBRE LOS AIRES AGUAS Y LUGARES - Galimberti Oliveira, María Cecilia (2017)
This paper studies the Hippocratic Treaty on Aires, Water and Places written by Hippocrates. The influence exerted by the environment in the individual's behavior, where the Hippocratic medical attention not only to the patient's body, but the entire cosmic universe: earth, water, climate, seasons and winds. We studied the prognostic view of Hippocratic medicine, based on rational knowledge of the disease and the relationship between diagnosis and prognosis. Finally, the treaty study the influence of anthropological theory when studying the cultural patterns of people, ways of thinking and acting, customs and character of the individual, a factor that must be taken into account by the Hippocratic physician.